A Person-Centered Approach to Social Media Addiction in Adolescents: Latent Profile Analysis of the Sense of Coherence, Cognitive Flexibility, and Emotion Regulation - Kaya, Bilal; Cenkseven Önder, Fulya (Addicta: The Turkish Journal on Addictions, 2025)
Social media addiction has become a widespread issue. Consequently, identifying the factors that mitigate social media addiction is of significant importance. The goal of this study was to explore how sense of coherence, cognitive flexibility, and emotion regulation are associated with social media addiction and to examine how profiles based on these variables differ in relation to social media addiction. Data were collected from 415 adolescents (mage = 16.36, standard deviation = 1.31), and profiles were identified using latent profile analysis. The analysis revealed three distinct profiles: “igh sense of coherence, cognitive flexibility, internal functional and external functional emotion regulation,” “edium sense of coherence, cognitive flexibility, internal functional and external functional emotion regulation,” and “low sense of coherence, cognitive flexibility, internal functional and external functional emotion regulation.” The results indicated that sense of coherence, cognitive flexibility, and emotion regulation were negatively associated with social media addiction. Additionally, the high profile demonstrated lower levels of social media addiction compared to the medium and low profiles, while the medium profile exhibited lower levels of social media addiction than the low profile. These findings suggest that prevention and intervention programs generated by salutogenic theory could play a role in reducing and preventing social media addiction.